Synchronizing Holocene lacustrine and marine sediment recordsusing paleomagnetic secular variation - Olafsdottir, S.; Geirsdottir, A.; Miller, Gifford; Stoner, J.; Channell, J. (Geological Society of America, 2013)
High sediment accumulation rates in lacustrine and shallowmarine archives around Iceland offer the potential to compare highresolution paleoclimatic reconstructions from terrestrial and marinearchives; however, direct comparisons are hampered by diffi culties in stratigraphic correlation and in deriving accurate age models for lacustrine archives. Icelandic paleomagnetic secular variation (PSV)has the potential to synchronize these records. Here we compare Holocene PSV from a well-dated marine core on the North Iceland shelf with PSV from two lacustrine archives with comparable sediment-accumulation rates, HVT03–1A, a glacier-dominated lake, and HAK03–1B, in a nonglacial catchment. Geochemically characterized tephra layers combined with unique high-amplitude structures in thePSV records provide secure tie points every ~200 yr. Once the records are synchronized, the chronology from the marine core can be reliably transferred to the two lacustrine records. The resultant lacustrine age models reveal large changes in sediment accumulation rate at submillennial scales that escape detection in conventional age models with independent dates every ~1 k.y. Sediment accumulation rate changes occur at similar times in both lakes, despite very different catchment properties. Low and regular accumulation rates during the Holocene thermal maximum suggest regionally stable, vegetated catchments, followed by a stepped landscape destabilization during the transition into neoglaciation, culminating with maximum sedimentation rates during the Little Ice Age. PSV allows synchronization between multiple records from nearby marine and lacustrine archives, providing improved age models and a means of assessing leads and lags between marine and terrestrial environments.